2003
DOI: 10.1097/00004770-200304000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Endodontic Sealers on Enterococcus faecalis

Abstract: Enterococcus faecalis has been shown to be highly resistant once established in the root canal system and may play an important role in endodontic failures. The purpose of this study was to evaluate the antimicrobial activity of four root canal sealers on E. faecalis. Seventeen blood-agar plates were inoculated with E. faecalis using the Lawn technique. Five discs were placed on each plate, four with sealers--Sealapex, Roth 811, Kerr EWT, and AH-Plus--and an ampicillin disc as the control. The plates were incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
1
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 9 publications
8
72
1
8
Order By: Relevance
“…However, eugenol below its minimum inhibitory concentration (sub-MIC) has been demonstrated to reduce the virulence properties such as adherence and biofilm formation of the cariogenic bacteria [47,48]. In addition other studies have demonstrated the effect of eugenol on a variety of oral bacteria causing disruption in cell membrane permeability [49] and proton pumps [50] that reduce microbial resistance and biofilm formation on dental materials, which explains the well-known bacteriostatic properties shown in other eugenol containing materials commonly used in dentistry such as zinc oxide eugenol cements and eugenol based root canal sealers [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, eugenol below its minimum inhibitory concentration (sub-MIC) has been demonstrated to reduce the virulence properties such as adherence and biofilm formation of the cariogenic bacteria [47,48]. In addition other studies have demonstrated the effect of eugenol on a variety of oral bacteria causing disruption in cell membrane permeability [49] and proton pumps [50] that reduce microbial resistance and biofilm formation on dental materials, which explains the well-known bacteriostatic properties shown in other eugenol containing materials commonly used in dentistry such as zinc oxide eugenol cements and eugenol based root canal sealers [51].…”
Section: Discussionmentioning
confidence: 99%
“…1,29 Poggio et al 17 used ADT with freshly mixed endodontic sealer (Endomethasone C, Argoseal, Bioseal Normal, Acroseal, AH Plus, Sicura Seal) after 24 and 48 h, and found low antibacterial activity for AH Plus in the periods tested. Wang et al 23 evaluated the proportions of dead and live bacteria inside the dentinal tubules after exposure to root canal sealers by confocal laser scanning microscopy, and reported antimicrobial activity for AH Plus after 1 and 7 days, unlike the results of the present study, which found no antimicrobial activity after 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…8 Sealapex and Acroseal are sealers containing calcium hydroxide, and their dissociation into calcium and hydroxyl ions alkalinize the environment, leaving it unfavorable to bacterial proliferation. 1 Moreover, calcium ions can react with carbon dioxide and reduce the breathing source of anaerobic bacteria. 9 AH Plus is a sealer with antimicrobial activity against F. nucleatum, P. gingivalis, 10 and E. faecalis.…”
Section: E Faecalis Is Also Ablementioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, its results are highly influenced by the diffusibility of the material across the medium. [6,12,13] Therefore, aim of the present study is to evaluate the antimicrobial activity of different root canal sealers against E.faecalis and C.albicans using agar diffusion method.…”
Section: Introductionmentioning
confidence: 99%